"Why didn't we do it"? Reproductive loss and the problem of post-mortem consent. (May 2021) - Reed, Kate; Ferazzoli, Maria Teresa; Whitby, Elspeth
Abstract: Informed consent has been a much debated topic within the social sciences. It often forms a central feature of discussions on research in medical settings and in social research methods more broadly. While sympathetic to its' underlying principles of autonomy and choice, social scientists have tended to argue that these are seldom enacted in research or clinical practice. Rather, such principles are often circumscribed by wider social structures and by a culture of medical dominance. Drawing on data from a qualitative study on perinatal post-mortem, this paper explores informed consent in the emotionally charged clinical arena of perinatal pathology. Our in-depth analysis will provide fresh insight into post-mortem decision-making in the sensitive arena of baby loss. Our findings show how parents often found it difficult to give consent for post-mortem, and also for professionals to take consent from parents. It was also not uncommon for parents to experience regret over non-consent later on. One of our key findings, however, related to the sense of emotional and diagnostic closure often afforded by post-mortem when consent had been given. We conclude by arguing that, although we cannot resolve the tension between the principles of consent and their enactment in practice, we can develop a reflexive approach with which to navigate the process. In doing so, the paper contributes to wider sociological discussions on the meaning and use of informed consent in various settings beyond medical contexts. Highlights: Informed consent is widely debated in social research and in clinical practice. Post-mortem consent after baby loss is difficult for parents and professionals. Informed consent can reinforce rather than abate medical paternalism. Post-mortem can offer parents a sense of emotional and diagnostic closure. A reflexive approach could assist professionals to better navigate the consent process.